La descripción de las partes de la oración en las artes del cachiquel. Métodos y fuentes. - García Aranda, María de los Ángeles (El Colegio de México, 2018)
This article presents and analyzes the descriptions of the parts of the sentence in Cachiquel (name, pronoun and indeclinable parts of the sentence) made in colonial times (1523-1821) in texts by Domingo Basseta, Francisco de la Parra, Benito de Villacañas, Francisco Ximénez, Carlos José Rosales, José Ildefonso Flores and Esteban Torresano. It also studies the context in which they were written and the sources that inspired them. The article hopes in this way to contribute to our understanding of missionary linguistics, their circumstances, methods and traditions.